2020
DOI: 10.1155/2020/7350781
|View full text |Cite
|
Sign up to set email alerts
|

Association between Renal Podocalyxin Expression and Renal Dysfunction in Patients with Diabetic Nephropathy: A Single-Center, Retrospective Case-Control Study

Abstract: This retrospective study investigated whether podocalyxin expression in renal biopsies and urine of patients with diabetic nephropathy (DN) is associated with renal function. This retrospective study included 32 patients with nephropathy, secondary to type 2 diabetes treated at the First Hospital of Lanzhou University (January 2010 to January 2015). Compared with the control group, the DN group had a significantly lower renal expression of podocalyxin and higher urinary podocalyxin/creatinine ratio. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
8
0
2
Order By: Relevance
“…eGFR typically reflect impaired renal function only in the advanced stages of DN. In recent study, similar finding on correlation between eGFR and u-PDX was demonstrated [32].…”
Section: Discussionsupporting
confidence: 73%
“…eGFR typically reflect impaired renal function only in the advanced stages of DN. In recent study, similar finding on correlation between eGFR and u-PDX was demonstrated [32].…”
Section: Discussionsupporting
confidence: 73%
“…[18]. Данный показатель отражает повреждения клубочкового аппарата почек, при этом происходит усиленное выделение подоцитов с мочой [19]. Исследования ряда авторов показали, что подоцитурия развивается у 74% больных с нормоальбуминурией и 54% с микроальбуминурией, с одинаковой частотой при I и II типах СД [20].…”
Section: Discussionunclassified
“…проходит две стадии альбуминурии [21]. Таким образом, наши данные подтверждают ранее проведенные исследования о росте этого показателя у больных с ДН [19,20].…”
Section: Discussionunclassified
“…Another study reports a heterozygous nonsense mutation in podocalyxin gene (c.C976T; p. Arg326X) that is characterized by proteinuria and renal insufficiency (189). Interestingly, a strong association was found between poor renal outcome and reduction of podocalyxin expression with an increase in its urinary excretion (342). Thus, assessment of podocalyxin levels in renal tissues and urine was proposed as a reliable biomarker to predict the progression of DN.…”
Section: Glomerulusmentioning
confidence: 99%